CATEGORIZATION OF STUDENT ERRORS IN SOLVING INTEGRAL PROBLEMS - Marhayati, Marhayati; Farida, Siti (Proceeding of International Conference on Islamic Education (ICIED); Vol 3 No 1 (2018): Proceeding of International Conference on Islamic Education (ICIED), 2018)
This research aims to categorise and describe students' errors in solving integral problems. This study was conducted on students of the second semester of mathematics education majoring in 40 students. Data retrieval is obtained by giving a test. The results of student work are grouped according to errors that appear from the results of the problem-solving. The categorization of student errors in solving integral problems obtained from this study are (1) errors in the selection of problem solving strategies, (2) errors in sampling, (3) error in integration is the addition of a constant (C) to the integral of course, and (4) errors in calculation because not careful.